Will Tattersdill, Science, Fiction, and the Fin-de-Siècle Periodical Press. Cambridge: Cambridge University Press, 2016, pp. x + 220, £67.99 cloth, £29.99 paper. ISBN: 978-1107144651. Issue 1 (2019) - James, Simon J.
No abstract available